PENERAPAN STRATEGI ACTIVE LEARNING TIPE INDEX CARD MATCH (ICM) DISERTAI TOPICAL REVIEW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 1 RAO SELATAN KABUPATEN PASAMAN - Amarta, Yumrizal; Rismen, Sefna; Lovia, Lita (STKIP PGRI Sumbar, 2013)
This research of background by studentâs livelines is lack and comprehension of math concept are still low at seventh grade students SMPN 1 South Rao. This research aims to determinethe studentsâ comprehension of math concept in seventh grade students SMPN 1 South Rao that applyÂ active learningÂ strategies Index Card Match type accompanied of Topical Review better than studentsâ comprehension of math concept that apply conventional learning. The type of research is experimental by using randomized control group only design. The techniques of sample collection taken by randomly. Research instrument in the form of final tes. The kind of test that used is essay with test reliability 0,886. The techniques of data analysis using the t test. The result of hypothesis test obtained Â and Â because the Â more than Â then the hypothesis in this research received. In conclusion, studentâs comprehension of math concept that apply active learning strategies Index Card MatchÂ type accompanied by Topical Review better than studentâs comprehension of math concept that apply conventional learning.